(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The researchers conducted this study to determine the level of acceptability of squash friend flavored with sour cream and onion. The researchers chose to use squash fries, sour cream, and onion flavors as the main ingredients of the product because these are more nutritious compared to other snacks that teenagers eat nowadays. The researcher chose a survey questionnaire as a method because the information the researchers can gather from the respondents is easy to present. The researchers selected 25 boys and 25 girls who took part in a survey by filling out the questionnaire. According to the findings, using squash as one of the major ingredients to make the product met expectations. The respondent’s evaluation as a predicted variable has no significance for the results. To make the texture crispy, coat it in cornstarch. To make it taste salty and sour, coat it in sour cream and onion powder. Respondents assessed the acceptability of the product in terms of taste and presentation as very satisfactory, and aroma, texture, size, smell, and quality as satisfactory. This study will focus on the acceptability of sour cream and onion-flavored squash fries. This may entail determining whether the responders find the appearance, smell, and flavor satisfactory. This may include the precise flavor, such as how sour, bitter, or salty it is, in order to change the proportion of ingredients used in the sour cream and onion-flavored squash fries.